Reconstruction of Tax Collection in a Fair Bankruptcy Process in Indonesia - Januardo Sulung P Sihombing; Ignatius Pradipa Probondaru; I Gede Yudi Arsawan (Faculty of Law, Universitas Pekalongan, 2025)
The preamble of the 1945 Constitution of the Republic of Indonesia expresses the hope for a prosperous of the Republic of Indonesia. Achieving this prosperity nation requires adequate state revenue, with taxes playing a crucial role. However, taxes are closely tied to the sustainability of a healthy economy. On the path to a prosperous nation, many businesses face bankruptcy, which often leads to delays in tax debt payments. According to bankruptcy, in refer to article 21 of the KUP Law, tax bills are prioritized over other debts. However, there remains a dual interpretationbregarding the hierarchy of creditor payments duringbthe bankruptcy process. Therefore, the state, through itsbtaxation authority, has a responsibility to ensure that taxes—a vital source of state revenue—are accounted for in bankruptcy proceedings. This ensures that the state does not lose a critical source of income needed to distribute tax benefits and maintain public welfare. This study aims to offer insights into the fairness of tax bill settlements within the bankruptcy process. The findings indicate that there is a need for equitable tax collection in bankruptcy cases in Indonesia.